Factors of QTc interval prolongation in patients with arterial hypertension - N. Ye. Tselik; O. V. Bilchenko (Zaporožskij Medicinskij Žurnal)
The relevance of determining the factors of the prolonged QTc interval development in patients with arterial hypertension is high, as it solves the issue of preliminary diagnosis among patients from risk groups and allows adjusting the diagnostic and therapeutic tactics of managing such patients.